Arab and Malay Students' Attitudes toward Statistics and Their Learning Styles: A Rasch Measurement Approach. (4th January 2022) - Fayomi, Aisha; Mahmud, Zamalia; Algarni, Ali; Almarashi, Abdullah M.
Abstract : Students' learning of statistics has been studied from a variety of angles, and this study is no different. The main purpose is to compare the Malay and Arab students' attitudes toward learning statistics and their learning styles in understanding statistics. A survey questionnaire and face-to-face interview techniques were used to elicit information from 150 students based on the cohort. They were asked about how they learn to solve statistical problems based on Kolb's four learning cycles: feeling, reflective observation, thinking, and doing. Attitude responses were numerically recorded based on a five-point Likert scale, while preference for learning styles was recorded as 1 (Do and Feel) or 0 (Watch and Think). Both attitude and learning style data were combined and subjected to Rasch analysis. Results show that a majority of the Arab and Malay students have moderate to high positive attitude toward learning statistics. Generally, students from both cultures are classified as the "Accommodating" type with a preference for doing and feeling from the experience of doing statistical problems. Arab students are classified as the "Assimilating" type with a preference for thinking, reflecting, and learning from observation, while Malay students are classified as the "Converging" type with a preference for thinking and doing statistical exercises.